DEVELOPMENT OF STRATEGY FOR REAL ESTATE PORTFOLIO MANAGEMENT - V. F. Volodko; V. V. Liashenko (Наука и техника)
The paper considers methodological principles to manage profitability of investor’s portfolio. In order to understand more perfectly the given problem the paper also contains main notions of the portfolio theory, formulation of the postulates that have been used for development of the portfolio theory, peculiar features concerning determination of estate investment profitability, definition of stages required for real estate portfolio formation; investment characteristics of real estate, factors exerting influence on investment profitability in the real estate portfolio.